Ethics of the Gift - Bayer, Oswald (Vox Scripturae - Revista Teológica Internacional, 2025)
In this article, there is a critical dialogue with the philosophy of modernity, especially with the Kantian tradition of the categorical imperative, on the subject of ethics. At first, an approach to the theme of ethics is made from the philosophy of religion, defending an understanding of ethics as a categorical gift. As a counterpoint to Kant, it is argued that the pre-ethical and aesthetic dimensions precede the ethical dimension. What is ethical is understood within the concepts of receiving and transmitting forward, inspired in 1 Cor 15.3. It is understood that ethics covers an asymmetry between what the person receives and what he gives of himself. In a second moment, one begins with the theological explanation of ethics, developing themes such as “reality of creation as a gift”, “deliver and receive the holy supper”, “Christ as gift”, “the verb: the process of giving” “Gift and promise”. In a third moment the concept of gift ethics is widely developed. The article represents a contribution to the theological foundation of ethics, based on a critical dialogue with the philosophy and philosophy of religion.